ANALISIS PERBANDINGAN EFEKTIVITAS TERAPI MUSIK KLASIK MOZART DENGAN TERAPI MUSIK INSTRUMENTAL POP TERHADAP INTENSITAS NYERI PADA PASIEN POST OPERASI COLOSTOMY DI RUMAH SAKIT MURNI TEGUH MEMORIAL HOSPITAL - Ningrum, Shintia Azhara; Lam Murni Br Sagala (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Background: The nursing problem that will arise in post colostomy surgery patients is pain. The management of post colostomy pain care that can be carried out by nurses for colostomy patients is by using non-pharmacological techniques such as Mozart classical music therapy and pop instrumental music. Purpose: To analyze the comparison of the effectiveness of Mozart classical music therapy with pop instrumental music therapy on pain intensity in postcolostomy surgery patients. Methods: This research is a quasi experiment with a two group pretest posttest design. The research was conducted at Murni Teguh Memorial Hospital. Total population of 79 patients and samples obtained as many as 28 people who were divided into 2 groups of 14 people each. Withdrawal of samples by purposive sampling. Analysis was performed univariately and bivariately using paired sample t-test and independent sample t-test. Results: There were differences in pain levels before and after giving Mozart classical music therapy to colostomy postoperative patients at Murni Teguh Memorial Hospital, p = 0.000 <0.05. There were differences in pain intensity in post colostomy surgery patients before (pretest) and after (pretest) given pop instrumental music therapy, p = 0.000 <0.05. There is a difference between Mozart classical music therapy and pop instrumental music therapy in reducing pain in post colostomy patients, p = 0.015 <0.05. Conclusion: Mozart's classical music therapy is more effective in reducing post colostomy pain than pop instrumental music therapy. Suggestion: It is suggested to Murni Teguh Memorial Hospital to make a policy through Standard Operating Procedures (SPO) regarding the provision of Mozart classical music therapy to postoperative patients.